IMPLEMENTASI PERATURAN DAERAH KOTA BOGOR NOMOR 13 TAHUN 2005 TENTANG PENATAAN PEDAGANG KAKI LIMA DI KOTA BOGOR - Afifah, Nurul; Rahmawati, Rita; Purnamasari, Irma (Administratie: Jurnal Administrasi Publik, 2019)
The number of street vendors in the city of Bogor continues to increase every year, namely 4.129 in year 2018. Its existence causes problems including security, comfort, cleanliness, beauty and order. For this reason, the need for structuring by implementing the Bogor city regulation number 13 in 2005. This study aims to determine the implementation of Bogor City regulation number 13 in 2005 concerning the arrangement of street vendors in the city of Bogor. The policy implementation theory used is theory according  to edward III there are four dimensions of policy implementation, namely communication (communication), resources (resources), attitude (disposition or attitude), and bureaucratic structure ( bureaucratic structure). The methode used is qualitative. The analysis use used is descriptive  using the weight mean scorefomula (WMS). The sampling technique is by purposive sampling. Those who are in zonning30 street vendors and outside zonning 10 street vendors, beside that, the saturated sampling technique is used for sample employees in the cooperatives and SME offices of Bogor city. The results of the study obtained a value of 3.671 with GOOD interpretation criteria. However, the facility indicator scored 3.40 with a GOOD ENOUGH interpretation. So the authors give advice, structuring street vendors is increased especially in terms of facilities and also the budget. So that from an adequate budget an increase in facilities, both electricity, water and extensiveand is created to sell.